2018
DOI: 10.3892/mmr.2018.9419
|View full text |Cite
|
Sign up to set email alerts
|

Aloperine inhibits proliferation, migration and invasion and induces apoptosis by blocking the Ras signaling pathway in human breast cancer cells

Abstract: Aloperine (Alo), as a quinolizidine alkaloid extracted from S. alopecuroide, has the positive activities of anti-inflammatory, anti-allergenic, antitumor and anti-viral. However, the role and mechanism of Alo in breast cancer have not been studied yet. In the present study, Alo markedly inhibited the proliferation and suppressed the colony formation ability of the breast cancer cell lines MCF-7 and MDA-MB-231 in a dose-dependent manner by Cell Counting kit-8 and colony formation assays, respectively. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…Studies performed with PC-3 cells revealed that ERβ-selective agonist DPN decreased the expression of N-cadherin [52] which is consistent with what was observed by us-downregulation of N-cadherin in the presence of isoflavones. Because ERβ activation was also related with the induction of apoptosis in PC-3M cells, apoptotic cell death may result not only from cytotoxic activity of extract components, but also could be used as functional link for agonistic aglycons binding to ERβ protein [53]. On the other hand, studies performed on the submandibular gland of the rat (an extensive postnatal development model) revealed that by biochanin A was involved in ERβ expression up-regulation [54].…”
Section: The Influene Of Trifolium Pratense L On Gene Expressionmentioning
confidence: 99%
“…Studies performed with PC-3 cells revealed that ERβ-selective agonist DPN decreased the expression of N-cadherin [52] which is consistent with what was observed by us-downregulation of N-cadherin in the presence of isoflavones. Because ERβ activation was also related with the induction of apoptosis in PC-3M cells, apoptotic cell death may result not only from cytotoxic activity of extract components, but also could be used as functional link for agonistic aglycons binding to ERβ protein [53]. On the other hand, studies performed on the submandibular gland of the rat (an extensive postnatal development model) revealed that by biochanin A was involved in ERβ expression up-regulation [54].…”
Section: The Influene Of Trifolium Pratense L On Gene Expressionmentioning
confidence: 99%
“…For instance, ALO exhibits anti-tumor activity on human thyroid cancer, as proven by its inhibitory effects on cell growth in human anaplastic thyroid cancers and multidrug-resistant papillary thyroid cancers [16]. ALO inhibits proliferation, migration and invasion and induces apoptosis in human breast cancer cells [24]. ALO executes anti-tumor effects on prostate cancer through the induction of apoptosis and cell cycle arrest both in vitro and in vivo [15].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of respiratory diseases, intragastric administration of 40 mg/kg of aloperine can improve lung function, alleviate asthma symptoms, and inhibit inflammatory responses in asthmatic mice. e mechanism is related to the regulation of the NF-κB inflammatory signal pathway and the reduction of TNF-α and IL-1β levels [51].…”
Section: Piperidine Alkaloidsmentioning
confidence: 99%